Uganda's post-colonial privatisation policy in higher education: an integrative literature review and case study analysis - Allan Muganga; Oluwasegun Adesola Oladipo; Michael Agyemang Adarkwah (Springer, 2024)
Abstract Globally, the trend toward privatizing higher education has been accelerating, driven by economic and policy shifts. Uganda has aligned with this movement, becoming one of the African countries implementing privatization to enhance accessibility and efficiency in its universities. However, the benefits and challenges of higher education privatization in Uganda remain underexplored. This study assesses them through two private universities as case studies. An integrative literature review identified challenges in Uganda's privatization policy. This was followed by qualitative interviews with sixteen (16) stakeholders (students, n = 10; parents, n = 3; employers, n = 3) to assess its impact on accessibility, quality, funding, and employment. Semi-structured interviews involving students, parents, and employers revealed that although the policy led to the massification of higher education, it also led to the commodification and academisation of education, whereby business principles have been imported into the country's higher education sector, thus focusing more on profit maximisation other than quality education delivery. The study recommends that the Ugandan government and policymakers, such as the Ministry of Education and Sports and the National Council for Higher Education, do more to safeguard the education system from being too commercialised, commodified, and over-marketised.